The Influence of Trust, Convenience and Risk on Decisions to Purchase Beauty Products Online Via E-Commerce (Case Study of UIN Raden Fatah Palembang Student) - Tanti Rosa Diyan Pratiwi; Mulyani Rizki; Safitri Asrol (Yayasan Adra Karima Hubbi, 2024)
The purpose of this study was to analyze the influence of trust, convenience and risk on online beauty product purchasing decisions through e-commerce of UIN Raden Fatah Palembang students. This study uses a quantitative research design aimed at consumers or users of e-commerce shopee, tiktok shop and facebook on UIN Raden Fatah students. with a data collection method using a questionnaire. for sampling in this study in the form of probability sampling with a sampling technique using a simple random sampling technique of 100 people with the help of IBM SPSS 26 program analysis. The results of this study indicate that trust has a positive and significant effect on the decision to purchase beauty products through e-commerce. Convenience has a positive and significant effect on the decision to purchase beauty products through e-commerce. Risk has a positive and significant effect on the decision to purchase beauty products through e-commerce. Simultaneously, trust, convenience and risk together have a positive and significant effect on the decision to purchase beauty products online through e-commerce on UIN Raden Fatah Palembang students.